Private secondary school principals in the city and province of Davao a survey into their personal characteristics and their supervisory functions - Cruz, Benedicto Vizcarra 1922- (s.n.], 1965)
This study provides a description of the personal characteristics of private secondary school principals in the City and Province of Davao and their supervisory functions.